Kurniawati, Zeny Analysis of Proximatic Levels and Sensory Quality of Organic Fish Feed from Fermented Coconut Drain Flour and Maggot Flour - Kurniawati, Zeny; Asngad, Aminah (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Background: The rise of fish farming has caused the market price of feed to increase by up to 60% of the production cost, so fish farmers need a breakthrough in new fish feed to reduce the production cost of fish farming activities. Methods: The type of experimental research with a Completely Randomized Design (CRD) and factorial design. There was one treatment factor and two repetitions, and each was carried out with three treatments on the fermented coconut dregs flour and maggot flour formulations, namely M1, M2, and M3. Feed testing was carried out by proximate testing of protein and carbohydrate content and hedonic quality testing for panelists with color, aroma, and texture parameters. Results: The results of the proximate test of the protein content of fish feed formulas M1, M2, and M3 were 7.83%, 11.64%, and 9.04%, respectively. In contrast, the carbohydrate content of fish feed formulas M1, M2, and M3 were 29.26%, 23.08%, and 27.84%, respectively. Meanwhile, the color sensory test results of formula M1, M2, and M3 feed have subsets of 2.00, 3.55, and 3.35, respectively. The results of the aroma sensory test of formula M1, M2, and M3 feed have subsets of 2.65, 3.40, and 3.35, respectively, while the results of the texture sensory test of formula M1, M2, and M3 feed have subsets of 2.65; 3.70; and 3.25 respectively. Conclusions: Formula M2 has the highest protein content of 11.64%, and formula M1 has the highest carbohydrate content of 29.26%.